Clinical impact of pancreaticoduodenectomy for pancreatic cancer with resection of the secondary or later branches of the superior mesenteric vein. (22nd July 2020) - Honda, Masayuki; Nagakawa, Yuichi; Akashi, Masanori; Hosokawa, Yuichi; Osakabe, Hiroaki; Takishita, Chie; Nishino, Hitoe; Tsuchida, Akihiko
Abstract: Purpose: To evaluate the feasibility of pancreaticoduodenectomy with resection of the second jejunal vein (J2V) for pancreatic ductal adenocarcinoma (PDAC). Methods: Among 114 patients with PDAC undergoing pancreaticoduodenectomy with portal‐superior mesenteric vein resection (PVR), surgical outcomes, and prognoses of 10 patients with resection of J2V or later branches of the superior mesenteric vein (J2VR) were compared to 104 patients with PVR above J2V (standard PVR). The reconstruction methods in the J2VR group were reviewed. Results: There were no significant differences in the operative time (470 vs 435 min), morbidity (30% vs 27%), presence of portal vein stenosis (10% vs 5%) or thrombosis (10% vs 1%), and induction of adjuvant therapy (80% vs 88%) between the J2VR and standard PVR groups, although blood loss was higher in the J2VR group (1184 vs 494 ml; P  = .002). R0 proportion and 2‐year survival rates were not significantly worse in the J2VR group compared to the standard PVR group (90 and 88%; 67 and 45%, respectively). At least one branch of the superior mesenteric vein was reconstructed in the J2VR group. Conclusion: Pancreaticoduodenectomy with J2VR for PDAC can be safely performed with a satisfactory overall survival rate. Abstract : Highlight Honda and colleagues analyzed the outcomes of pancreaticoduodenectomy for pancreatic ductal adenocarcinoma with resection of the secondary or later branches of the superior mesenteric vein. They concluded that the procedure is safe and has satisfactory overall survival rates. Although technically difficult, resection should not be abandoned for such pancreatic cancer.